Cultured Hepatocytes Adopt Progenitor Characteristics and Display Bipotent Capacity to Repopulate the Liver. Issue 7 (July 2014) - Krause, Petra; Unthan-Fechner, Kirsten; Probst, Irmelin; Koenig, Sarah
Clinical studies have proved the therapeutic potential of hepatocyte transplantation as a promising alternative to whole organ liver transplantation in the treatment of hereditary or end-stage liver disease. However, donor shortage seriously restricts cell availability, and the lack of appropriate cell culture protocols for the storage and maintenance of donor cells constitutes a significant obstacle. The aim of this study was to stimulate mature hepatocytes in culture to multiply in vitro and track their fate on transplantation. Rat hepatocytes isolated nonenzymatically were cultured serum free for up to 10 days. They were stimulated into proliferation in the presence of growth factors and conditioned media from nonparenchymal and hepatocyte culture supernatants, as well as 10 mM lithium chloride (LiCl). Cell proliferation was assessed by determining DNA content. Additionally, the extent of cell differentiation was estimated using immunofluorescence staining of hepatic, biliary, progenitor, and mesenchymal markers and gene expression analyses. Transplantation studies were performed on the Fischer CD26-mutant rat following pretreatment with retrorsine and partial hepatectomy. Proliferating hepatocytes increasingly adopted precursor characteristics, expressing progenitor (OV6, CD133), hepatic lineage (CK18), biliary (CD49f, CK7, CK19), and mesenchymal (vimentin) markers. The supplement of LiCl further enhanced the proliferative capacity by 30%. Transplantation studies revealed extensive repopulation by large donor hepatocyte clusters. Furthermore, bile duct-like structures deriving from donor cells proved to be immunoreactive to ductular markers and formed in close proximity to endogenous bile ducts. Mature hepatocytes reveal their potential to "switch" between phenotypes, adopting progenitor characteristics during proliferation in vitro. Following transplantation, these "retrodifferentiated" cells further expanded in vivo, thereby generating bipotentially differentiated progenies (hepatocytes and bile duct-like structures). This apparent plasticity of mature hepatocytes may open new approaches for cell-based strategies to treat liver disease.